Abortion in Judaism - Schiff, Daniel, Dr (Cambridge University Press, 2002)
Abortion in Judaism presents a complete Jewish legal history of abortion from the earliest relevant biblical references through the end of the twentieth century. For the first time, almost every Jewish text relevant to the abortion issue is explored, providing important insights into the development of Jewish ethical principles.